IgG In Saliva, GCF, and Serum in Young Patients With Grade C Molar Incisor Pattern Periodontitis - Meaad M. Alamri; Gordon Proctor; Luigi Nibali (Clinical and Experimental Dental Research)
ABSTRACT Objective This cross‐sectional study aimed to investigate immunoglobulin G levels in saliva, gingival crevicular fluid, and serum samples from young patients with grade C molar incisor pattern periodontitis (C/MIP) and age‐matched periodontitis‐free controls. Methods Saliva, gingival crevicular fluid, and blood samples were collected from 62 patients, divided into 31 cases and 31 periodontitis‐free age‐matched controls. Saliva and blood samples were centrifuged to extract supernatant and serum. Gingival crevicular fluid periopapers were eluted. Human total immunoglobulin G levels were assessed using an Enzyme‐Linked Immunosorbent Assay. Results After adjusting for covariates, cases had higher Immunoglobulin G levels in saliva (p = 0.005), gingival crevicular fluid (p < 0.001) than controls; however, serum did not reach the significant threshold (p = 0.137). Among other factors contributing to immunoglobulin G levels, males had higher serum immunoglobulin G than females (p = 0.018), and serum immunoglobulin G levels increased with age (p = 0.033). Gender and ethnicity subgroup analyses revealed that C/MIP males had higher saliva IgG (p = 0.018) than control males, and both genders had higher GCF IgG than controls (p ≤ 0.001). C/MIP Caucasians had elevated saliva (p = 0.011) and GCF IgG p = (0.003) compared to the controls, and Asians had higher GCF IgG than the controls (p = 0.011). Conclusion This study shows for the first time that C/MIP cases have higher Immunoglobulin G levels than controls in saliva and gingival crevicular fluid, confirming its association with C/MIP pathogenesis and suggesting that it could be a potential biomarker in grade C molar incisor pattern periodontitis. Further research on a larger sample size is needed.